Smart Word-Searching System (SWSS) / Tan Yin Pin - Tan, Yin Pin (2002)
All undergraduate students of the Faculty of Computer Science and Information Technology (FSKTM), University of Malaya are required to carry out a Final Year Thesis Project in computer or information technology related of preparation in real working environment. I assigned to do research in Smart Words-Searching System as it provided more efficient way for user in daily working environment especially for those text-interface employee who have to face the monitor for text edit or typing. The Smart Words-Searching System was developed using Visual Basic as the main tools of development, where it was used to build interface and function need in the system. Visual Basic, famous in creating sophisticated professional application, is an easy-to-use application and it can be integrated with most of the Microsoft tools such as Microsoft Access, which is used as a database to store all data and information required for the system. The methodology part have been decided to use the most widely understand that the WaterFall model. The five steps easy to implement and maintenance and it is effective against any product implementation. The literature review makes use of some similar products or systems in the market. For the global usage, like the Ms word of the Microsoft cooperation and search engine in the World Wide Web. The search can be include Boolean search functions for users to search for the texts or phrases they need to modify or something else.